Blocking copper transporter protein-dependent drug efflux with albumin-encapsulated Pt(IV) for synergistically enhanced chemo-immunotherapy - Man Fang; Lei Cao; Zhao Zhang; Zhen Yu; Yue Shen; Jieqi Chen; Juan Chen; Yue-Qin Li; Zhaoqian Liu; Yingcai Meng; Haihua Xiao; Qiang Qu; et al. (Journal of Nanobiotechnology)
Abstract Non-small cell lung cancer (NSCLC) represents the most prevalent form of lung cancer, exerting a substantial impact on global health. Cisplatin-based chemotherapy is the standard treatment for NSCLC, but resistance and severe side effects present significant clinical challenges. Recently, novel tetravalent platinum compounds have attracted significant interest. While numerous studies concentrate on their functional modifications and targeted delivery, tumor-induced platinum resistance is frequently overlooked. Previous tetravalent platinum compound demonstrated antitumor activity, yet proved ineffective against cells exhibiting resistance to cisplatin. In order to enhance the efficacy and potential applications of tetravalent platinum in NSCLC, a glutathione (GSH)-responsive albumin nanoquadrivalent platinum (HSA@Pt) have been constructed. In light of previous research into drug conjugation, this study was to develop a combined chemo-immunotherapy approach. The HSA@Pt demonstrated high efficacy and low toxicity, with targeted tumor accumulation. Furthermore, Ammonium Tetrathiomolybdate (TM) has been demonstrated to exert a synergistic inhibitory effect on ATPase Copper Transporting Beta (ATP7B) and Programmed Death Ligand 1 (PD-L1), impede platinum efflux, induce cellular stress, and activate antitumor immunity. The findings suggest HSA@Pt’s potential for clinical use and a novel chemo-immunotherapy strategy for NSCLC, enhancing the utility of established drugs through synergistic sensitization.